Study-related wellbeing, behavior, and attitudes of university students in the Netherlands during emergency remote teaching in the context of COVID-19: A longitudinal study - Vollmann, Manja; Scheepers, Renée A.; Nieboer, Anna P.; Hilverda, Femke (Frontiers in Psychology, 2022)
During the COVID-19 pandemic, emergency remote teaching was implemented at all Dutch universities; however, the degree of limitations in on-campus teaching and learning varied during the pandemic dependent on the strictness of the measures. In the present study, it will be investigated how study-related experiences of university students changed in the face of varying limitations in on-campus teaching and learning. The study had a longitudinal natural experiment design with three points of measurement during the academic year 2020-2021: November-December 2020 (t1; campuses partially open), March 2021 (t2; campuses fully closed) and June-July 2021 (t3; campuses partially open). In total, 680 Dutch university students (65.9% female; age: M = 21 years, SD = 2.06) filled in online surveys measuring study-related well-being (academic burnout and study-engagement), study-related behavior (study effort), and study-related attitudes (education satisfaction, online self-efficacy, and attitudes toward online education). Overall, students reported moderate levels of academic burnout, study engagement, study effort, education satisfaction, and online self-efficacy; their attitudes toward online education were rather negative. Students’ study-related well-being and education satisfaction decreased in the period when on-campus teaching and learning was impossible (t2) compared to periods in which on-campus teaching and learning was possible at a low level with several restrictions (t1 and t3). Students’ attitudes toward online education and online self-efficacy slightly increased at the end of the academic year (t3); however, the attitudes toward online education remained negative. The findings indicate that students’ academic burnout, study engagement, and education satisfaction varied over the course of the academic year in the context of changing limitations in on-campus teaching and learning. To facilitate positive study-related experiences, universities are advised to offer as much on-campus education as possible in times of pandemics.